A Novel Technical Refinement of Microvascular Decompression: Pain Relief and Complication Rate in a Consecutive Series of Patients With Trigeminal Neuralgia. (18th December 2021) - Tomasello, Francesco; Germanò, Antonino; Lavano, Angelo; Romano, Alberto; Cafarella, Daniele; Gorgoglione, Nicola; La Torre, Domenico
Graphical Abstract: